Comparative in-vitro evaluation of ebastine tablets (10 mg) available in bangladesh (Bangladesh Journal of Medical Science, 2024)
Background: The symptoms of allergic responses, such as hay fever or urticaria, can be relieved with the use of ebastine, an efficient anti-allergic medication.Objective & Method: This study’s primary objective was to assess and contrast various quality control parameters, such as weight variation, % friability, hardness, disintegration time, dissolution profile, and potency, of the twelve different brands of Ebastine tablets that were readily available in Bangladesh in accordance with compendia procedures. It’s interesting to note that, according to various official requirements, all of the quality parameters indicated above were within acceptable bounds.Conclusion: Therefore, doctors can advise patients to use any of the Ebastine brands that are sold in Bangladesh.Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 47-53